ICE manual of highway design and management - Walsh, Ian D. (ICE, 2011)
The 'ICE Manual of Highway Design and Management' is a one-stop reference for all practising engineers working in the field of highway engineering.
Keywords: Highway engineering -- Great Britain -- Handbooks, manuals, etc.; Great Britain.; elektronické knihy; electronic books